2020
DOI: 10.1063/1.5113847
|View full text |Cite
|
Sign up to set email alerts
|

Trace level toxic ammonia gas sensing of single-walled carbon nanotubes wrapped polyaniline nanofibers

Abstract: This paper presents a two-step enhancement and a comprehensive analysis of single-walled carbon nanotubes (SWCNTs) wrapped polyaniline nanofiber (NPANI) ammonia (NH3) gas sensor at room temperature. SWCNT-PANI composites are successfully synthesized using an efficient and cost-effective rapid in situ chemical polymerization method. The structural morphology and modification of the samples are characterized using field-emission scanning electron microscopy and HRTEM. FTIR and Raman spectroscopic studies are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The chemisorptions can take place by site defect on the CNTs sidewall. [22,23] As it is reported that the binding energy of chemisorbed ammonia is quite high [24] ; and their desorption from the surface of CNTs need some external excitation energy to the system. [25] The Kong et al found that adding ammonia significantly altered the electrical resistance of sc-SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…The chemisorptions can take place by site defect on the CNTs sidewall. [22,23] As it is reported that the binding energy of chemisorbed ammonia is quite high [24] ; and their desorption from the surface of CNTs need some external excitation energy to the system. [25] The Kong et al found that adding ammonia significantly altered the electrical resistance of sc-SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, chemiresistors based on nanostructured polymers (e.g., polypyrrole (PPy), polyvinyl alcohol (PVA), polyaniline (PAN), poly (aniline co-pyrrole) (PAP), polystyrene (PS), poly 3,4-ethylene dioxythiophene (PEDOT), and cationic polyacrylamide (CPAM)) of desired functionality and conductivity continue to enhance NH 3 sensing performance [ 10 , 28 , 29 , 30 , 31 ]. Polymer-based NH 3 sensors are popular for miniaturized configuration, user, and environmentally friendly, tunable chemistries, low-cost, flexibility, and energy efficiency.…”
Section: Exploring Needs Of Ammonia Detection and Monitoring: Introductionmentioning
confidence: 99%
“…Polymer-based NH 3 sensors are popular for miniaturized configuration, user, and environmentally friendly, tunable chemistries, low-cost, flexibility, and energy efficiency. However, owing to the high affinity of polymers toward humidity and volatile organic compounds present in the environment, it exhibits poor stability and cross-sensitivity [ 10 , 28 , 29 , 30 ].…”
Section: Exploring Needs Of Ammonia Detection and Monitoring: Introductionmentioning
confidence: 99%
“…The sensing mechanism is complex and different with different polymers, i.e., when a reducing gas such as NH 3 interacts with the reactive sites of the emeraldine base of PANI, protonation/ deprotonation of PANI occurs and NH 4+ ions are formed owing to the delocalization of electrons and increase in the electronegativity on its surface. 90 4. CNM hybrid nanocomposite-based gas sensors…”
Section: Sensing Mechanism Of Cnm Hybrid Nanocompositesmentioning
confidence: 99%